2021
DOI: 10.1002/app.51894
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of bio‐plasticizer and core–shell rubber on poly(lactic acid) toughness for sustainable flexible packaging applications

Abstract: Poly(lactic acid) (PLA) toughness was improved by blending with tributyrin (TBR) and poly(methyl methacrylate-co-ethyl acrylate) core-shell rubber (CSR) for toughening purpose. PLA was prepared by melt processing as binary (PLA/TBR or PLA/CSR) and ternary (PLA/TBR/CSR) blends with the total additive contents from 5 to 20 wt%. Ratios of TBR:CSR for the ternary blend were 25:75, 50:50, and 75:25. Based on the experimental results, a suitable formulation for the flexible packaging application was the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is well known that the slow crystallization rate of PLA leading to low crystallinity is the main cause of its poor heat resistance. The addition of nucleating agents is a simple and efficient method to increase the crystallization rate and improve the crystallinity of polymers [30][31][32]. Among various nucleating agents, fibers have distinct advantages due to their ability to promote polymer crystallization and significantly strengthen the matrix of the polymer, resulting in composite materials with excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the slow crystallization rate of PLA leading to low crystallinity is the main cause of its poor heat resistance. The addition of nucleating agents is a simple and efficient method to increase the crystallization rate and improve the crystallinity of polymers [30][31][32]. Among various nucleating agents, fibers have distinct advantages due to their ability to promote polymer crystallization and significantly strengthen the matrix of the polymer, resulting in composite materials with excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to make up the shortcoming of insufficient toughness of polymers, the common way is by blending flexible material into the polymers as toughening phase, such as elastomers, [6][7][8][9][10] core-shell tougheners, [11][12][13] and other flexible or elastic polymer. [14][15][16] Wu et al 17 reported that the incorporation of polypropylene (PP) and maleic anhydride grafted styrene-ethylene-butylene-styrene (SEBS-g-MA) could efficiently toughen polyamide 6 (PA6) due to the formation of core-shell structures in PA6 matrix.…”
Section: Introductionmentioning
confidence: 99%